2019
DOI: 10.1111/ldrp.12194
|View full text |Cite
|
Sign up to set email alerts
|

Paraphrasing Interventions and Problem‐Solving Accuracy: Do Generative Procedures Help English Language Learners with Math Difficulties?

Abstract: This randomized control treatment study investigated the role of generative paraphrasing interventions on word problem‐solving (WPS) accuracy in English language learners (ELL) who were at risk for math difficulties (MD). One hundred and forty‐two third‐grade monolingual and English language learners were randomly assigned to either an untreated control group or one of three treatment conditions: paraphrase question (Restate), paraphrase relevant information (Relevant), and paraphrase all propositions (Complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Kong and Swanson et al (2019) conducted a combined multiple baseline and criterion changing design to examine the effectiveness of a paraphrasing intervention on improving the accuracy of WPS for nine third‐grade ELs at risk of mathematics disabilities. The intervention involved teaching students to identify the question, find the relevant information, cross out irrelevant information, and solve and check answers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kong and Swanson et al (2019) conducted a combined multiple baseline and criterion changing design to examine the effectiveness of a paraphrasing intervention on improving the accuracy of WPS for nine third‐grade ELs at risk of mathematics disabilities. The intervention involved teaching students to identify the question, find the relevant information, cross out irrelevant information, and solve and check answers.…”
Section: Resultsmentioning
confidence: 99%
“…In most studies, reading comprehension instruction was embedded in the mathematics interventions, such as paraphrasing or restating word problems, pre‐teaching vocabulary and mathematics concepts, distinguishing relevant information, and more, all of which benefited ELs with LDM in solving mathematical word problems (Kingsdorf & Krawec, 2016; Kong & Swanson, 2019; Moran et al, 2014; Swanson et al, 2019). Some studies did not explicitly include reading comprehension instruction in their interventions, but strategies such as modelling or non‐verbal or non‐textual drawing to represent mathematical relations described in word problems facilitated students' reading comprehension and benefited ELs with LDM (Sharp & Shih Dennis, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages of ELs included in the samples varied across studies. Three studies reported that ELs accounted for more than 50% of their samples (Clarke et al, 2014;Moran et al, 2014;Swanson et al, 2019), while in four studies fewer than 10% of the participants were ELs (Bryant et al, 2011;Fuchs et al, 2008;Jitendra et al, 2009;.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…In the last 20 years, the number of English Language Learners (ELs) in the public schools has grown substantially. According to the educational data, ELs made up 10.1% of the school–age population in the fall of 2017, with nearly 75% of these children having Spanish as their first language, or L1 (U.S. Department of Education, Institute of Education Sciences, National Center for Education Statistics, 2020). It is expected that by 2025, 25% of students in the schools will be ELs, increasing to 40% by 2030 (Santiago & Brown, 2004).…”
mentioning
confidence: 99%